Trump, Brexit and the crisis of the liberal world order - Pribićević, Ognjen (Teorija in praksa, 2020)
The article aims to analyse the relationship between President Trump's new policies, Brexit and the crisis of the liberal international order. The author's main hypothesis is that the current liberal order is in serious crisis. While Brexit may be described as the biggest change in European politics since the fall of the Berlin Wall, it is argued that Trump's new foreign policy is the most important change in world politics since the Second World War. President Trump is the first American President since then to: 1) choose moderate isolation over cooperation and multilateralism; 2) not promote democracy as a vital feature of US foreign policy; 3) be actively hostile to liberal internationalism; and 4) hold different views to his predecessors on the issues of trade, alliances, the environment, and international law. The author concludes that the world is heading towards a new international order that features the USA, China and Russia as the key player
Keywords: ameriška zunanja politika; Brexit; Donald Trump; Foreign policy; kriza demokracije; Liberalism; Liberalizem; liberalni mednarodni red; Nedemokratičnost; New economic order; Nondemocratic stand; Novi ekonomski red; velesile; Zunanja politika